KAPASITAS MANAJEMEN KEWIRAUSAHAAN DAN KINERJA ORGANISASI - M, Arlennora (Jurnal Ilmu Administrasi Negara, 2013)
Capacity Management of Entrepreneurship and Organizational Performance. This studyaimed to determine the effect of the macro environment, organizational culture, regional endowmentand entrepreneurial management capacity on organizational performance. The study design usingquantitative methods with a sample of 48 official Department of Cooperatives and Small and MediumEnterprises Province Riau. Data were collected through a questionnaire and analyzed using pathanalysis techniques using SPSS for windows. The results showed that the influence of the macroenvironment, organizational culture, regional endowment directly on organizational performance isvery weak (not significant). Influence of macro environment, organizational culture and endowmentregions on organizational performance can be significantly over capacity variable entrepreneurialmanagement. Strong direct influence on organizational performance is entrepreneurial managementcapacity but overall macro environmental influences, organizational culture, regional endowmentand entrepreneurial management capacity on organizational performance is still weak and only gavethe contribution to the performance of the organization as much as 7.61%. The findings of thisstudy show needs to do further research on other factors that predominantly affects organizationalperformance such as motivation, professionalism and entrepreneurial spirit.Key words: entrepreneurial management, performance, public entrepreneurship, reinventing local government.